A phase-transfer assisted solvo-thermal strategy for low-temperature synthesis of Na3(VO1−xPO4)2F1+2x cathodes for sodium-ion batteries1. Issue 33 (28th April 2015) - Zhao, Junmei; Mu, Linqin; Qi, Yuruo; Hu, Yong-Sheng; Liu, Huizhou; Dai, Sheng
<x xml:space="preserve">Abstract</x> A series of Na3(VO1−xPO4)2F1+2x (x = 0, 0.5 and 1) compounds with superior Na storage performance can be synthesized by a phase-transfer assisted solvo-thermal strategy at a rather low temperature (120 °C) in one simple step.